Energy transition and sustainable development in Malaysia: Steering towards a greener future - Ghosn, Fadi; Zreik, Mohamad; Awad, Ghina; Karouni, George (International Journal of Renewable Energy Development, 2024)
In the evolving landscape of global energy dynamics, Malaysia stands as a pivotal example of a nation actively transitioning towards renewable energy and sustainable development. This paper provides a comprehensive analysis of Malaysia's energy sector transformation, underpinned by the government's commitment to reducing carbon emissions and mitigating the impacts of climate change. The objective of this research is to delve into the intricacies, opportunities, and challenges of steering Malaysia towards a greener future, with a particular focus on the shift from reliance on fossil fuels to the adoption of renewable energy sources such as solar, wind, and biomass. Employing a mixed-method approach, this study synthesizes existing literature, policy documents, and case studies to examine the current state and historical context of energy use in Malaysia, analyze government initiatives and policy frameworks, explore technological advancements, and assess the environmental and socioeconomic impacts of the energy transition. Results indicate that despite facing challenges such as financial investment, technological advancement, and public acceptance, collaborative efforts between the government, private sector, and communities have led to significant progress in promoting renewable energy. The paper concludes that Malaysia's energy transition represents a critical step towards achieving a balance between economic growth and environmental preservation, setting a precedent for sustainable development in the Southeast Asian region. This transition is not only essential for climate change mitigation but also presents opportunities for economic diversification, energy security, and social inclusivity. The study ultimately calls for continued innovation, supportive policies, and international cooperation to overcome remaining barriers and fully realize the potential of renewable energy in Malaysia.